Metaphor and irony in the constitution of UK borders: An assessment of the 'Mac' cartoons in the Daily Mail newspaper. (May 2019) - Robson, Matthew
Abstract: Popular culture is irrevocably implicated in the political constitution of borders, geographical space and identity. Whether this takes the form of re-affirming, or challenging the borders and identities that have reached a hegemonic status will depend, amongst other things, on power, knowledge, subjectivity and ethics. Recently, a monumental struggle has been taking place in the UK over precisely these questions, with a view to deciding the nation-state's future as either situated within or outside the European Union. This article seeks to contribute to the themes briefly outlined here by analysing how the 'Mac' cartoons in the Daily Mail newspaper have approached the issue of (im)migration. A central focus will be placed on the ostensible use of metaphor and irony in these cultural items, which are used to constitute contingent concepts as literal and as 'real': for instance the UK border, the British identity and the (im)migrant Other identity. Yet more than that, this article seeks to contribute to existing studies on editorial cartoons by drawing attention to how 'Mac' not only denigrates the (im)migrant Other identity, but concurrently constitutes the British Self as 'complacent, ' 'passive' 'ignorant' and even 'foolish.' This is carried out as 'Mac' puts forward his case for stronger UK border controls.